Diagnostic accuracy of conventional oral examination for detecting oral cavity cancer and potentially malignant disorders in patients with clinically evident oral lesions: Systematic review and meta‐analysis. Issue 4 (29th January 2022) - Essat, Munira; Cooper, Katy; Bessey, Alice; Clowes, Mark; Chilcott, James B.; Hunter, Keith D.
Abstract: This systematic review evaluates the diagnostic accuracy of conventional oral examination (COE) versus incisional or excisional biopsy for the diagnosis of malignant and/or dysplastic lesions in patients with clinically evident lesions. Searches were conducted across five electronic databases from inception to January 2020. Meta‐analyses were undertaken, where appropriate. Among 18 included studies, 14 studies were included in the meta‐analysis, giving summary estimates for COE of 71% sensitivity and 85% specificity for the diagnosis of dysplastic and/or malignant lesions. The pooled diagnostic accuracy of identifying malignant‐only lesions was reported in seven studies, giving a pooled estimate of 88% sensitivity and 81% specificity. Diagnostic accuracy of different types of dental/medical professionals in identifying dysplastic or malignant lesions gave varying estimates of sensitivity and specificity across three studies. Further research is needed to improve the diagnostic accuracy of COE for early detection of dysplastic and malignant oral lesions.